Linear multi-level programming problems with random variables - Sinha, S. B.; Sinha, Surabhi (Opsearch, 2004)
In this paper we study hierarchical systems with stochastic data: be it the cost coefficients, right-hand-side vector, coefficient matrix or any of their combinations. The problem is converted to its equivalent deterministic form using any known stochastic approach. This deterministic model (in case of a linear hierarchy) may be linear or nonlinear depending on which parameter in the problem is random. Finally the linear nonlinear deterministic model is solved using fuzzy technique [9] via linear membership function. We have also shown the application of the deterministic models to find a solution using numerical examples.